2012
DOI: 10.1586/eri.12.38
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial chemotherapy ofMycoplasma genitalium-positive non-gonococcal urethritis

Abstract: Mycoplasma genitalium is an important pathogen of acute non-gonococcal urethritis (NGU) in men and plays a significant role in persistent or recurrent NGU. In the management of patients with M. genitalium-positive NGU, eradication of the mycoplasma from the urethra is necessary to prevent persistent or recurrent NGU. Therefore, M. genitalium should be considered for antimicrobial chemotherapy of NGU. This article reviews the in vitro antimicrobial activities of antibiotics against M. genitalium and the efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…It has been reported that the rates of eradication of M. genitalium from NGU patients treated with levofloxacin or ofloxacin tend to be inferior to those obtained with gatifloxacin or moxifloxacin (34). In this study, gatifloxacin and moxifloxacin were shown to exhibit more-potent inhibitory activities than levofloxacin against all topoisomerases tested, including mutant topoisomerase IV.…”
Section: Discussionmentioning
confidence: 60%
“…It has been reported that the rates of eradication of M. genitalium from NGU patients treated with levofloxacin or ofloxacin tend to be inferior to those obtained with gatifloxacin or moxifloxacin (34). In this study, gatifloxacin and moxifloxacin were shown to exhibit more-potent inhibitory activities than levofloxacin against all topoisomerases tested, including mutant topoisomerase IV.…”
Section: Discussionmentioning
confidence: 60%
“…These seven men were excluded from the analyses of the demographic and clinical characteristics of monomicrobial NGU and all-examined microorganism-negative NGU. The characteristics of 22,14,21,12, and 11 men with NGU positive only for MG, UU, HI, AV and HSV-1 or HSV-2, respectively, and 29 men with NGU negative for all microorganisms examined were compared with those of the 110 men positive only for CT (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The DOXY regimens are not effective on MG-positive NGU. 21 Recently, we have reported the emergence and increase of MG clinical strains harboring mutations in the 23S rRNA gene associated with macrolide resistance and/or those in the parC gene associated with fluoroquinolone resistance. 29 The single-dose regimen of azithromycin 1 g or extended-release azithromycin 2 g failed to eradicate MG strains with the mutant 23S rRNA gene in some cases of NGU, but the regimen of sitafloxacin 100 mg twice daily for 7 days was still effective on NGU caused by MG strains with the mutant parC gene.…”
mentioning
confidence: 99%
“…Azithromycin regimens have been recommended for the treatment of M. genitalium infections, but recently, azithromycin treatment failures have been observed [2]. Moxifloxacin regimens have been highly effective for persistent M. genitalium infections unsuccessfully treated with azithromycin [2].…”
Section: Introductionmentioning
confidence: 99%